Calculation of the electron-optical scheme of a new type mirror energy analyzer of charged particles - Kambarova, Zh.T.; Saulebekov, A.O.; Kopbalina, K.V. (Karagandy University of the name of acad. E.A. Buketov, 2022)
Further studies of the electron-optical properties of electrostatic multipole-cylindrical fields, synthesized from the fields of a cylindrical mirror and circular multipoles, are continued in the work. The implementation of electron spectroscopy methods is based on the use of complex equipment, one of the main elements of which is an electron energy analyzer of low and medium energies. Application of the multipole approach to the synthesis of deflecting fields makes it possible to develop effective methods for energy analysis of charged particle beams. The electron-optical scheme of new type mirror energy analyzer of charged particle beams based on an electrostatic axially symmetric octupole-cylindrical field is proposed in the work. An axially symmetric octupole-cylindrical field is constructed as a superposition of a basic cylindrical field and a circular octupole. When the fields were added, the central circle of the octupole was combined with the zero equipotential of the logarithmic field. The motion of charged particles in the electrostatic octupole-cylindrical field. An integrodifferential equation for the motion of charged particles in an electrostatic octupole-cylindrical field is derived. Calculation of trajectories in an energy analyzer with an octupole-cylindrical field was performed on the basis of the method of expansion into a fractional-power series of the particle motion equation presented in the integrodifferential form. Coefficients of the series, representing the trajectory of motion in an analytical form, accessible for further studies of the electron-optical characteristics of the octupole-cylindrical field, are obtained. Based on an octupole-cylindrical field, high luminosity energy analyzers can be built to determine the composition of charged particle beams with energies from units of eV to tens of keV in space plasma.
Жаңа типті зарядталған бөлшектердің айналы энергия талдағыштың электронды-оптикалық сұлбасын есептеу
Расчет электронно-оптической схемы зеркального энергоанализатора заряженных частиц нового типа
Keywords: energy analyzer of charged particles; electron mirrors; electrostatic axially symmetric octupole-cylindrical field; approximate-analytical calculation; motion of charged particles